Overview of the Juvenile Diversion and Mediation Program - Lado Javakhishvili (Alternative Dispute Resolution Yearbook, 2016)
More and more countries encounter necessity and relevance of restorative justice concept in the modern world. Georgia is no exception in this regards. The clear example of this tendence is Juvenile Diversion and Mediation Program incluclated in Georgia in 2010, the results of which appear of utmost interest of various countries. The hereby work provides history of development of diversion and mediation program in Georgia. The article also considers the principles of the program, legal regulation issues. We will also find the detailed statistics of the program. The hereof issues obtain particular relevancy against the background of juvenile justice code, enacted on January 1, 2016.